2019
DOI: 10.3346/jkms.2019.34.e159
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Associated with Obstructive Coronary Artery Disease in Patients with Out-of-Hospital Cardiac Arrest: Data from the Korean Cardiac Arrest Research Consortium (KoCARC) Registry

Abstract: Background Although coronary artery disease (CAD) is a major cause of out-of-hospital cardiac arrest (OHCA), there has been no convinced data on the necessity of routine invasive coronary angiography (ICA) in OHCA. We investigated clinical factors associated with obstructive CAD in OHCA. Methods Data from 516 OHCA patients (mean age 58 years, 83% men) who underwent ICA after resuscitation was obtained from a nation-wide OHCA registry. Obstructive CAD was defined as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…Patients suffering out-of-hospital cardiac arrest, those with old age, hypertension, positive cardiac enzyme, and initial shockable rhythm were associated with obstructive coronary artery disease. Early invasive coronary angiography should be considered in these patients [14].…”
Section: Hemodynamic and Cardiac Managementmentioning
confidence: 99%
“…Patients suffering out-of-hospital cardiac arrest, those with old age, hypertension, positive cardiac enzyme, and initial shockable rhythm were associated with obstructive coronary artery disease. Early invasive coronary angiography should be considered in these patients [14].…”
Section: Hemodynamic and Cardiac Managementmentioning
confidence: 99%
“…For patients with refractory CA without ROSC, current guidelines recommend an urgent coronary angiography only if it appears logistically feasible and if an acute coronary syndrome is suspected 1 . Shockable primary rhythm is associated with both cardiac cause for collapse 16 and improved outcome in ECPR 17 and is consequently one of the factors in favor of ECPR initiation 6 . In addition, logistics in a catheterization laboratory appear ideal for www.nature.com/scientificreports www.nature.com/scientificreports/ rapid, sterile, effective, and safe cannulation to establish VA-ECMO under CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Although relevant studies had shown that initial shockable rhythm was closely associated with the prognosis of patients with cardiac arrest, 21‐23 We used a nonshockable initial rhythm instead of initial shockable rhythm in our study. The reasons were as follows: (a) nonshockable initial rhythm could be quickly recorded before cardiac arrest occurred because nonshockable initial rhythm taken a relatively long time to develop into cardiac arrest 24 ; (b) the most of the initial shockable rhythm of cardiac arrest were developed from nonshockable initial rhythm 24 ; (c) The time that initial shockable rhythm developed into cardiac arrest was concise, as a result, that the discover and diagnose the initial shockable rhythm with very difficult neither in or out of the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…if tracheal intubation and ventilator were given in time, hypoxemia could not be quickly relieved, and more importantly, a simple respirator was the first and most frequently received respiratory support devices, which with poor respiratory support. 20 Although relevant studies had shown that initial shockable rhythm was closely associated with the prognosis of patients with cardiac arrest, [21][22][23] We used a nonshockable initial rhythm instead of initial shockable rhythm in our study. The reasons were as follows:…”
Section: Verification Of Prediction Modelmentioning
confidence: 99%